2017
DOI: 10.1002/btpr.2418
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Tubespins as a suitable scale‐down model of bioreactors for high cell density CHO cell culture

Abstract: High cell density (HCD) culture increases recombinant protein productivity via higher biomass. Compared to traditional fed-batch cultures, HCD is achieved by increased nutrient availability and removal of undesired metabolic components via regular medium replenishment. HCD process development is usually performed in instrumented lab-scale bioreactors (BR) that require time and labor for setup and operation. To potentially minimize resources and cost during HCD experiments, we evaluated a 2-week 50-mL Tubespin … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
24
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(25 citation statements)
references
References 20 publications
0
24
0
1
Order By: Relevance
“…This procedure was performed on a daily basis over 14 days to evaluate the maximum VCD at a constant perfusion rate of 1 RV/day. Similar procedures were presented before (Gomez et al, ; Sieck et al, ; Villiger‐Oberbek et al, ).…”
Section: Methodsmentioning
confidence: 88%
See 1 more Smart Citation
“…This procedure was performed on a daily basis over 14 days to evaluate the maximum VCD at a constant perfusion rate of 1 RV/day. Similar procedures were presented before (Gomez et al, ; Sieck et al, ; Villiger‐Oberbek et al, ).…”
Section: Methodsmentioning
confidence: 88%
“…Shake‐tube (ST) bioreactor systems represent a less expensive small‐scale reactor system (Jordan & Jenkins, ) that have been recently considered as suitable screening device for perfused cell culture systems (Gomez et al, ; Sieck, Schild, & von Hagen, ; Villiger‐Oberbek, Yang, Zhou, & Yang, ). In particular, the possibility of screening cell clones and media formulations in a daily discontinuous batch‐refeed mode has been demonstrated.…”
Section: Introductionmentioning
confidence: 99%
“…As mentioned above, when using STs as scale‐down model for batch and continuous processes (Gomez et al, ; Villiger‐Oberbek et al, ; Xie et al, ; Zhang et al, ), the most critical parameter for operation at high VCDs is sufficient gas liquid mass transfer, both oxygen supply and CO 2 removal. Considering the operation in an orbital shaken incubator the following parameters affect the gas transfer: Shaking diameter, shaking speed, filling volume, and shaking angle.…”
Section: Resultsmentioning
confidence: 99%
“…It has been shown that cell growth, peak viable cell density as well as titer are lower in this approach than in standard bench‐scale bioreactors. In terms of product quality, glycosylation was comparable but other attributes like deamidation and C‐terminal lysine clipping were found to be lower . Another study using this application of spin‐tubes showed a similar growth profile in spin‐tubes and a steady‐state perfusion bioreactor but higher lactate levels were observed.…”
Section: Introductionmentioning
confidence: 81%